2021
DOI: 10.1111/hiv.13190
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study of the impact of coronavirus disease (COVID‐19) on psychological and financial wellbeing and engagement in care among men who have sex with men living with HIV in Thailand

Abstract: Objectives The coronavirus disease (COVID‐19) pandemic is an unprecedented event with massive global health and socio‐economic impacts on vulnerable populations, especially people living with HIV. The epidemic has severely affected Thailand’s economy and potentially impacted the financial and psychological wellbeing of Thai HIV‐positive men who have sex with men (MSM). Methods Between 15 June and 10 December 2020, we conducted qualitative interviews with 26 MSM living w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 26 publications
2
21
0
Order By: Relevance
“…However, our results and findings by others may indicated that the prevalence of depression and anxiety were higher than before. There are studies indicated that anxiety and depression are related to COVID-19 [34,35], and for PLHIV who have more worry and anxiety about the COVID-19 pandemic because of impaired immune response and stigma surrounding if diagnosed with COVID-19, therefore, more provision of confidential care to PLHIV are needed, in consideration of the persistent existence of COVID-19 at present.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, our results and findings by others may indicated that the prevalence of depression and anxiety were higher than before. There are studies indicated that anxiety and depression are related to COVID-19 [34,35], and for PLHIV who have more worry and anxiety about the COVID-19 pandemic because of impaired immune response and stigma surrounding if diagnosed with COVID-19, therefore, more provision of confidential care to PLHIV are needed, in consideration of the persistent existence of COVID-19 at present.…”
Section: Discussionmentioning
confidence: 99%
“…Four hundred twenty-four PLHIV were enrolled, the mean age was 34 years (IQR, [30][31][32][33][34][35][36][37][38][39][40], 416 (98.1%) were male, and 398 (94.9%) were Han. The mean body mass index (BMI) was 22.8 kg/m 2 (IQR, 20.8-24.7).…”
Section: Baseline Characteristicsmentioning
confidence: 99%
“…Of the 27 selected studies, six were published [24-28] in 2020, when the pandemic was first declared. However, in 2021, 21 studies [8][9][10][11]16,23,[29][30][31][32][33][34][35][36][37][38][39][40][41][42][43], 3.5 times as many, were published-and publication is still ongoing. There is still insufficient research on men's mental health in the COVID-19 era.…”
Section: Discussionmentioning
confidence: 99%
“…Doctors and medical practitioners are not the only heroes during the pandemic; all researchers who have utilized their academic disciplines to provide assistance are also heroes [ 12 ]. Given that COVID-19 has affected many domains, particularly healthcare (HC), and left a knock-on effect on diagnoses and treatments [ 13 ], among other challenges, [ 14 ], people have become concerned with the future and strength of medical institutions should a similar pandemic hit us again in the future [ 15 ]. The World Health Organization (WHO) claims that evaluating and understanding pandemic-associated factors is crucial [ 16 ].…”
Section: Introductionmentioning
confidence: 99%